If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6(x + 4) = 3(x + 16) Reorder the terms: 6(4 + x) = 3(x + 16) (4 * 6 + x * 6) = 3(x + 16) (24 + 6x) = 3(x + 16) Reorder the terms: 24 + 6x = 3(16 + x) 24 + 6x = (16 * 3 + x * 3) 24 + 6x = (48 + 3x) Solving 24 + 6x = 48 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 24 + 6x + -3x = 48 + 3x + -3x Combine like terms: 6x + -3x = 3x 24 + 3x = 48 + 3x + -3x Combine like terms: 3x + -3x = 0 24 + 3x = 48 + 0 24 + 3x = 48 Add '-24' to each side of the equation. 24 + -24 + 3x = 48 + -24 Combine like terms: 24 + -24 = 0 0 + 3x = 48 + -24 3x = 48 + -24 Combine like terms: 48 + -24 = 24 3x = 24 Divide each side by '3'. x = 8 Simplifying x = 8
| 1/3(b+6)=1/4b | | 2377960+26d=3000000 | | -2x+3(2x-3)=-1 | | 14d+2=5d+56 | | -50=-5(3m-8) | | 65=7x-5 | | 2(3t+2)=10 | | 9-7x=-5 | | 66=7x-11 | | -2(4t-11)=-18 | | 3/2p-14+p+13 | | 3/2p-14=p | | -3(3+-7)=66 | | 6(x-6)=28.2 | | 2(x-4)=24-2x | | (x-4)=24-2x | | 31.4=2r*3.14 | | 9(a+2)=61.2 | | 11x+-4x=56 | | 45=5(2t+7) | | 8x-6x=49 | | 49.8=6c-3 | | 2377960+26d=730 | | 10x+11=111 | | 6p=23.4 | | 32+2a=6a | | 3(x-9)=-3 | | 9+c/-5=-5 | | 8e-2=14 | | 3x-3=85-8x | | x+9=3x+13 | | 7-5x=3x+12 |